The Effect of 8 Weeks Aerobic Training on the Social Adjustment in Mentally Retarded Children with Hemiplegic Cerebral Palsy - Zahra Pooraghaei Ardakani; Forough Rahmati (The Society of Aging and Physical Activity (SAPA), 2015)
One of the most important and basic problems in mentally retarded children which can form the basis of their behavior is impairment in social adjustment and performance. The purpose of the present work was to study the effect of 8 weeks aerobic training on the social adjustment in mentally retarded children with hemiplegic cerebral palsy. The statistical population included all mentally retarded children with hemiplegic cerebral palsy in District 1 of Tehran who were under the coverage of Exceptional Education Organization in 2013-2014 academic year. Among 38 mentally retarded children, 24 (with a mean age of 9±2 years) were randomly selected and divided into two groups: experimental and the control groups. To assess the social adjustment, Vineland Adjustment Behavior Scale (VABS) (1984) was used. Quasi-experimental method with pretest and posttest design and a control group was used for this research. The findings showed that 8 weeks aerobic exercises could increase the social adjustment in children with hemiplegic cerebral palsy (P≤0.001). Finally, it can be concluded that aerobic exercises have a positive impact on the social adjustment in children with hemiplegic cerebral palsy by increasing their communication with peers.